PENGARUH PARITAS TERHADAP PERSENTASE ESTRUS DAN KEBUNTINGAN SAPI PERANAKAN ONGOLE YANG DISINKRONISASI ESTRUS MENGGUNAKAN PROSTAGLANDIN F2Α (PGF2Α) - Arni Nadhirah Putri; Sri Suharyati; Purnama Edy Santosa (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The research aimed to determine the effect of parities on the percentage of estrous and conception of OngoleOffspring after estrous synchronization using prostaglandin F2α (PGF2α). The research was held in November2012until February 2013, located in Punggur District, Central Lampung Regency, Lampung Province.This research used Completely Randomized Design (CRD) with three treatments and four replications. Thetreatments were Ongole Offspring heifers (P0); Ongole Offspring which have calved once (P1); and OngoleOffspring which have calved twice (P2). Data of percentage of estrous and conception was analyzed by using Chisquareon level of 5%.The result of the Chi-square analysis showed that parity was not significantly different (P>0,05) to the percentage ofestrous and conception of Ongole Offspring. The estrous percentage of Ongole Offspring was 100%. The conceptionpercentages of Ongole Offspring on P0, P1, and P2 in a row were 25%, 0%, and 25%.